Couples’ Immigration Status and Ethnicity as Determinants of Breastfeeding - Gibson-Davis, Christina M. (© American Journal of Public Health 2006, 2006)
Objectives: We investigated how couples’ immigration status and ethnicity determined the decision to initiate breastfeeding and to breastfeed at 6 months. Methods: From data collected on 4207 mothers and 3013 fathers participating in a longitudinal birth cohort study, we used linear regression and covariate-adjusted proportions to estimate the determinants of breastfeeding behaviors. The sample was divided by immigration status (either foreign born or born in the United States) and further subdivided by ethnicity (Mexican Hispanic, non-Mexican Hispanic, and non-Hispanic). Results: Mothers born in the United States had an 85% reduction in the odds of breastfeeding as compared to foreign-born mothers and a 66% reduction in the odds of breastfeeding at 6 months. Each additional year of US residency decreased the odds of breastfeeding by 4%. These differences by immigration status were seen for Mexicans, other Hispanics, and non-Hispanics. Conclusion: The Hispanic paradox may extend to other non-Hispanic immigrants for breastfeeding behaviors, but may not be true for Hispanic mothers born in the United States. Low rates of breastfeeding for Hispanic American mothers indicate that they should not be overlooked by breastfeeding promotion programs.